Cervical cerclage for cervical insufficiency: methods and pregnancy outcomes at a tertiary hospital in South-Western Nigeria - Adebisi, Mathew O.; Adekanye, Emmanuel A.; Adeniyi, Adebayo A.; Afolabi, Oluwasesan B.; Okurumeh, Ogheneovo I.; Adeyemo, Olabisi T.; Adewara, Olumide E.; Awoyinka, Bbatunde S.; Bakare, Adewumi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: A ‘gold standard’ for the treatment of cervical insufficiency is by inserting cervical cerclage. This intervention may not be successful in all cases. Hence, there is a need to assess the methods and pregnancy outcomes of cervical cerclage, and draw conclusion from the findings. Objectives were to assess the methods and pregnancy outcome of cervical cerclage in women with cervical incompetence at the federal teaching hospital, Ido-Ekiti, Ekiti State. Methods: This is a 5-year retrospective review of the records of women that had cervical cerclage between June 2019 and June 2024. The data were retrieved and analyzed for their socio-demographic factors, clinical characteristics, landmark past clinical events, number of past cerclage insertions, and the methods and pregnancy outcomes of index cerclage. The data obtained were analyzed using SPSS version 26. Results: There were 27 cases of cerclage placement per 2,489 deliveries (1 in 92 births) during the period under review. The mean age was 33.6±4.8 years. Majority (74.1%) aged 31 to 40 years. Two-thirds of women (66.7%) had no prior births, 25.9% had one birth, and 7.4% had two or more births. The McDonald’s technique was the most commonly used method, accounting for 92.6% of cases. Favourable outcome was recorded in 85.2% of the women. Conclusions: This study showed that majority of the women treated with cerclage had successful pregnancy outcome, further supporting this intervention as a “gold standard” for managing cervical incompetence.